Manajemen Magang Industri Guru Produktif Teknik Komputer dan Jaringan di SMK Negeri Kabupaten Cilacap - Novie Herawati (Manajemen Pendidikan, 2021)
The research aimed to analyze the planning industrial apprenticeship of productive teachers in computer and network engineering at Vocational High School in Cilacap Regency, elaborate the problem in processing of apprenticeship computer and network engineering teacher at Vocational High School in Cilacap Regency, and to evaluate of industrial apprenticeship computer and network engineering teacher at Vocational High School in Cilacap Regency. This research was done in two Vocational High School which had done industrial apprenticeship for teacher expertise competence in computer and network, they were SMK N 1 Binangun and SMK N 1 Cilacap. The method used in research were descriptive with a qualitative approach. The research data obtained by obtaining some facts from direct interviewee. The research subjects were taken using random techniques based on area (Cluster Random Sampling), data collection validation technique using triangulation research evidence. Data analysis using interactive method by Miles Huberman that begun with data collection, reduction, data presentation and data verification. The results showed that the planning of internship work for productive TKJ teachers needed to be made technical instructions for internship activities, the implementation of the internship showed that the competence, implementation of K3, practical equipment in schools were not in accordance with industry standards, evaluation of apprenticeship activities included adding apprenticeship quota, upgrading teacher competence, synchronization equipment, industry standard curriculum. It is hoped that the next teacher internship research will be able to determine the time, competence, and standard internship equipment with the industry.